Ensuring Teaching Continuity: Chilean University Students’ Perception on Remote Teaching of English during COVID 19 Pandemic - Chuan Chih Hsu; Chia Shih Su; Kau I Su (Yayasan Visi Intan Permata, 2022)
The objective of our study is to know the perception of Chilean university students toward the pedagogical methodologies in online English classes during the COVID-19 pandemic. We applied a questionnaire (built by fifteen experts, validated through a pilot test of 34 students, and improved with licensed 21.0 version SPSS in terms of consistency) to 341 students from different university programs. We analyzed the responses quantitatively and qualitatively and found out that 75% of the 341 students surveyed have shown agreement with the pedagogical methodologies applied in online classes and motivation in learning due to the permanent concern and communication of the teacher in charge. Besides, the students have also yielded satisfactory learning outcomes. These results reveal that the online English teaching of Chilean higher education during the pandemic has been good and indirectly show the willingness of Chilean university teachers to receive relevant and continuous training to deliver quality education. In 2022, many countries have returned to face-to-face classes, but we believe that the pedagogical methodologies used in this research could serve as a reference for teachers or researchers worldwide who wish to incorporate into their face-to-face classes a part of online teaching and do research on online English teaching.